Transformasi Organisasi di Era Society 5.0: Inovasi, Adaptasi, dan Keterlibatan Manusia dalam Revolusi Teknologi - Aripin, Susi Susyanti; Imlakiyah, Iim; Suharyat, Yayat (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
In a volatile environment, organizations are challenged with increased uncertainty in various areas that can disrupt organizational sustainability. There is fear that there will be a complex and ambiguous uncertainty that an invasion could erode human character values. Human resources are the most valuable asset owned by an organization. The role of HR has urgency in contributing to increasing organizational development. To prepare ourselves to take part in inviting the time of society 5.0. This is an anticipation of disruption caused by Industrial Revolution 4.0. the scientific work results from a literature study that describes the important role of organizational development in preparing human resources in the technological era. thus, improving organizational development requires superior human resources which are considered the driving force of an organization that collectively contributes to achieving performance. To prepare oneself to face the contemporary era, two things should be done: adaptation and competence in mastering technology, being able to fundamentally, be imaginative, communicate, collaborate, and have problem-solving capasities.